Garbhagriha (sanctum sanctorum) of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) leads to the antarala (vestibule or antechamber), a shallow passage distinguished by pillars along its sides. From there, one proceeds to the garbhagriha (sanctum sanctorum) of the Undeshwar Temple, featuring a meticulously carved doorframe. This doorframe exhibits a multi-shakha (vertical band or architrave) design, with each shakha adorned with various floral patterns, naga (serpant) figures and stambha (buttress). At the lower part of the doorframe, there are four female figures, two of whom hold kalashas (pitchers) while the other two hold chauris (fly whisks). Following them are four-armed dvarapalas (door guardians), each depicted with their respective attributes. Lastly, there is a figure of Kubera holding a money bag. Above the lalatabimba (lintels) on the doorframe's entablature, Nataraja is positioned at the center, flanked by seated goddesses, with Brahma and Vishnu depicted at the ends.